The effectiveness of a training program based on virtual reality technology for improving joint attention among the children with autism spectrum disorder - Gaber, Sherif Adel (Journal of Educational and Psychological Sciences, 2022)
This study investigated the effectiveness of a training program based on virtual reality technology for improving joint attention among a sample of children with autism spectrum disorder who enrolled in the Autism Institute (Autism Program) in Al- Ahsa Governorate, Kingdom of Saudi Arabia whom ages ranged between (6- 9) years. A quasi- experimental approach used to investigate the effectiveness of the virtual reality technology program which developed by researcher. The results showed that there was statistical significant difference between the experimental and control groups in the post- test on joint attention and between its dimensions in favor of the experimental group, there was statistical significant difference between pretest- and- post- test of the experimental group in favor of the post- test. Whereas, the results showed that there were no statistical significant differences on the joint attention of the control group in the pre and post- test. There was no statistical significant difference on the joint attention of the experimental group between post- test and follow- up test for the experimental group.
Keywords: Virtual Reality Technology; °360 Technique; Joint Attention; Children with Autism Spectrum Disorder